A study on internet addiction among medical students in a tertiary care hospital in Bangalore, India - Lavadi, Raj; Subramanian, Mangala; Panchaseelan, Meghana; Chintala, Lakshmi; Reddy, Lalasa; Dhananjay, Megha; Acharya, Supriya (International Journal Of Community Medicine And Public Health, 2021)
Background: Internet usage is prevalent among medical students as they utilize it for both study purposes as well as for entertainment. Widespread usage of the internet may lead to its addiction. The objective of the study was to determine the prevalence of internet addiction and identify its contributing factors among medical students. Methods: 239 second and third year medical students completed the internet addiction test as well as the supplementary questionnaire at Vydehi institute of medical sciences and research center. The assessment of addiction was performed using Dr. Kimberley Young’s internet addiction test. Results: It was found that 120 (50.2%) students were mildly addicted and 39 (16.3%) students were moderately addicted and 1 (0.42%) student was severely addicted. Conclusions: 66.9% of medical students had various levels of internet addiction from mild to severe. Therefore, behavior change communication is required to overcome addiction in these students.